Menggali Pemikiran Filsafat Islam: Perbandingan Aliran Peripatetisme, Iluminasionisme dan Perenialisme - Fadhia Ananda; Mutohharun Jinan (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Islamic philosophy constitutes an intellectual tradition that has developed through a dynamic dialectic between revelation and reason in the pursuit of understanding metaphysical, cosmological, and anthropological realities. This article examines three major schools within Islamic philosophy Peripateticism, Illuminationism, and Perennialism which represent distinct epistemological and spiritual approaches to the quest for ultimate truth. Peripateticism, as developed by prominent figures such as al-Kindi, al-Farabi, Ibn Sina, and Ibn Rushd, emphasizes rational intellect and logical methodology as primary means of acquiring knowledge. Illuminationism, pioneered by Suhrawardi, integrates philosophical rationality with intuition and inner spiritual experience as legitimate sources of knowledge. Meanwhile, Perennialism, popularized by Seyyed Hossein Nasr, highlights the synthesis of reason, revelation, and intuition in the pursuit of universal and transcendent truth. This study employs a descriptive qualitative method with a library research approach to analyze relevant primary and secondary sources. The findings indicate that these three intellectual traditions have made significant contributions to the enrichment of Islamic philosophical discourse and offer conceptual frameworks that remain relevant in addressing contemporary intellectual and spiritual challenges